My "e" Sound Box - Moncure, Jane Belk; Thornburgh, Rebecca McKillip (Mankato, MN : Child's World, 2009)
Little e has an adventure with items beginning with his letter's sound, such as eggs, elves, and an elephant.
Keywords: Alphabet -- Fiction; Children's book